Analisa Prediksi Potensi Likuifaksi di Kota Rengat Kabupaten Indragiri Hulu - Yogi Septian Malik; Ayu Putri Permata (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The number of incidents occurring on the island of Sumatra, especially West Sumatera and Jambi provinces that affect the vibration of the earthquake in Rengat City on a large scale can lead to the movement of land such as landslides and stagnant ground water sources can lead to liquefaction. The purpose of this research is to know how the arrangement of soil type at research location Rengat City and to know the location reviewed in Rengat City, and its surrounding experience potential liquefaction based on some existing penetration test data. This research was conducted to predict liquefaction potential that occurred in Rengat City of Indragiri Hulu Regency with secondary data of penetration test of konus with Seed and Idriss method (1971). The calculation of potential liquefaction prediction is done by determining the number of soil layers, estimating the weight of the soil volume, determining the soil overburden, determining the effective soil stress, determining the corrected confront resistance, calculating Cyclic Strees Ratio (CSR), calculating Cyclic Resistance Ratio (CRR). After calculating the value of Magnitude Scalling Factor (MSF) and calculating the value of safe factor by comparing the value of Cyclic Strees Ratio (CSR) with Cyclic Resistance Ratio (CRR) if the calculation <1 factor is safe then potentially liquefaction occurs. Based on the results of the analysis of the 7 locations with a total of 2 cone penetration test conus analyzed in this study in Rengat City, obtained the type of soil structure is not uniform and based on the results of analysis, from the 7 research sites with tottal 21 point penetration test konus reviewed at magnitude 5 to 10 in Rengat City Indragiri Hulu Regency. In the type of sand soil in the dominant study area can not be achieved liquefaction, this is reinforced from the calculation (SF)> 1 safe factor (SF: 1.0).